2021
DOI: 10.1038/s41598-020-80787-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of Coronavirus Disease-19 mortality and prior bacille Calmette-Guerin vaccination: a robust ecological analysis using unsupervised machine learning

Abstract: Population-level data have suggested that bacille Calmette-Guerin (BCG) vaccination may lessen the severity of Coronavirus Disease-19 (COVID-19) prompting clinical trials in this area. Some reports have demonstrated conflicting results. We performed a robust, ecologic analysis comparing COVID-19 related mortality (CRM) between strictly selected countries based on BCG vaccination program status utilizing publicly available databases and machine learning methods to define the association between active BCG vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…Accordingly, there is a hypothesis that the substantial differences may be related to the universal BCG vaccination policies of these countries. Several ecological studies analyzed worldwide data before June 2020 and found that even after controlling for important country level factors such as temperature, total population size, population density, proportion of those aged 60 years or above, gross domestic product per capita, healthcare access and quality measures, COVID-19 testing numbers, and stringency level of the nationwide epidemic control policy, the BCG vaccination coverage rate and the total BCG vaccination implementation years among these countries are still significantly inversely correlated with the incidence and mortality of COVID-19 [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, there is a hypothesis that the substantial differences may be related to the universal BCG vaccination policies of these countries. Several ecological studies analyzed worldwide data before June 2020 and found that even after controlling for important country level factors such as temperature, total population size, population density, proportion of those aged 60 years or above, gross domestic product per capita, healthcare access and quality measures, COVID-19 testing numbers, and stringency level of the nationwide epidemic control policy, the BCG vaccination coverage rate and the total BCG vaccination implementation years among these countries are still significantly inversely correlated with the incidence and mortality of COVID-19 [5][6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Whether BCG vaccination could have a beneficial effect against COVID-19 also under intense debate. Several ecological studies did suggest the potential protective effect of the universal BCG vaccination program on reducing COVID-19 morbidity and mortality [5][6][7][8][9][10][11][12][13]; some also implied that different BCG strains might vary in their protective ability [14]. In contrast, the inverse relation between COVID-19 disease burden and BCG vaccination was not observed by others [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A multivariable analysis of COVID-19 death and case rates found a strong negative correlation between those rates and years of BCG administration and found the strongest effect to be in the youngest age group [ 100 ]. Unsupervised machine learning found that COVID-19 death rates were lower in countries that had a BCG vaccination policy for the previous 15 years, including in younger populations, but the same effect was not seen for other vaccination programs [ 101 ]. A total of 61 factors—including BCG vaccine coverage, percentage of urban population, and percentage with insufficient physical activity—were examined in 173 countries, using morbidity and mortality as outcomes, and found that recent BCG vaccine coverage reduced COVID-19 mortality, but not morbidity [ 102 ].…”
Section: Bcg and Covid-19: A Strategy To Reduce The Public Health Burden Of Epidemic Respiratory Disease?mentioning
confidence: 99%
“…We limited our analyses to determinants included in the OWID series, hence it is possible that additional factors might explain the TDPM differences observed between countries. For example, vaccination against Bacillus Calmette-Guerin (BCG) has been recently reported as protective against severe COVID-19 infection [39][40][41][42] . However, a recent work has reported that, similarly with several determinants we investigated, BCG vaccination exerts a strong protective effect against COVID-19 in the early stage of the pandemic while fading in later stages 43 .…”
Section: Namementioning
confidence: 99%